2022
DOI: 10.3390/s22020690
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Water Holdup in Vertical Upward Oil–Water Two-Phase Flow Pipes Using a Helical Capacitance Sensor

Abstract: Oil–water two-phase flows widely exist in industrial production, especially in the petroleum industry. The liquid holdup is significant for understanding reservoir production characteristics and improving oil recovery. This paper focuses on the helical capacitance sensor for the measurement of water holdup of oil–water two-phase flows. A new double helix capacitance sensor with an electrode rotation angle of 360° is designed. The sensitivity field distribution of the sensor with different parameters is simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…They found that there was a linear relationship between the sensor response and the water holdup for two-phase flow in a small pipe. Dai et al [32] designed a double helix capacitance sensor for vertical oil-water holdup measurement in a wide range of water cuts.…”
Section: Introductionmentioning
confidence: 99%
“…They found that there was a linear relationship between the sensor response and the water holdup for two-phase flow in a small pipe. Dai et al [32] designed a double helix capacitance sensor for vertical oil-water holdup measurement in a wide range of water cuts.…”
Section: Introductionmentioning
confidence: 99%
“…Oil-water two-phase flow is common in the process of oil and gas development and processing. It is very important to monitor its physical parameters in real time, especially in the process of electric dehydration, where the two parameters of conductivity and water cut (and the relationship between them) are key to establishing an effective dehydration electric field [1][2][3][4][5][6]. Therefore, this investigation studies the method and system of synchronous measurement of conductivity and water content by dual-frequency digital demodulation technology.…”
Section: Introductionmentioning
confidence: 99%